Precision-guided or blunt? The effects of US economic sanctions on human rights - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
We use endogenous treatment-regression models to estimate the causal average treatment effect of US economic sanctions on four types of human rights. In contrast to previous studies, we find no support for adverse effects of sanctions on economic rights, political and civil rights, and basic human rights. With respect to women's rights, our findings even indicate a positive relationship. Emancipatory rights are, on average, strengthened when a country faces sanctions by the US. Our findings are robust when applying various changes to the empirical specification. Most importantly, this study provides strong evidence that the endogeneity of treatment assignment must be modelled when the consequences of sanctions are studied empirically.
Keywords: F51; F52; F53; K10; K11; P14; P16; P26; 330; Democratization; Discrimination; Economic Sanctions; Endogenous Treatment Model; Human Rights; Interventionism; Protectionism; Repression; United States